2013
DOI: 10.1111/1556-4029.12324
|View full text |Cite
|
Sign up to set email alerts
|

Morphometric Comparison of Clavicle Outlines from 3D Bone Scans and 2D Chest Radiographs: A Shortlisting Tool to Assist Radiographic Identification of Human Skeletons

Abstract: This paper describes a computerized clavicle identification system primarily designed to resolve the identities of unaccounted-for U.S. soldiers who fought in the Korean War. Elliptical Fourier analysis is used to quantify the clavicle outline shape from skeletons and postero-anterior antemortem chest radiographs to rank individuals in terms of metric distance. Similar to leading fingerprint identification systems, shortlists of the top matching candidates are extracted for subsequent human visual assessment. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
46
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 41 publications
2
46
0
Order By: Relevance
“…Positive predictive values in serial shortlists for the clavicle matching program compared between the current study (black line; n am = 7361; n pm = 30; n A = 4) and Stephan et al (light gray line; n am = 409; n pm = 17; n A = 2). The bold vertical line highlights shortlist performance when comprised of 10% of the total sample.…”
Section: Methodsmentioning
confidence: 73%
See 3 more Smart Citations
“…Positive predictive values in serial shortlists for the clavicle matching program compared between the current study (black line; n am = 7361; n pm = 30; n A = 4) and Stephan et al (light gray line; n am = 409; n pm = 17; n A = 2). The bold vertical line highlights shortlist performance when comprised of 10% of the total sample.…”
Section: Methodsmentioning
confidence: 73%
“…Three charts of serial PPVs were generated: (i) PPVs for each of the four analysts and the overall mean for this study (Fig. ); (ii) the mean for this study ( n am = 7361; n pm = 30; n A = 4) compared to the mean performance observed by Stephan et al ( n am = 409; n pm = 17; n A = 2; Fig. ); and (iii) the mean performance of analysts and skeletal remains common between the two studies, that is, this study ( n am = 7361; n pm = 17; n A = 2), and that of Stephan et al ( n am = 409; n pm = 17; n A = 2; Fig.…”
Section: Methodsmentioning
confidence: 77%
See 2 more Smart Citations
“…Human body measurements have been used in the field of anthropology for inferring age and gender from skeletal remains [1][2], for inferring genetic population membership [3][4] and for individual identification in forensic anthropology [5]. More recently, body shape has been investigated as a biometric identifier.…”
Section: Introductionmentioning
confidence: 99%